(untitled) (Dhaka University Journal of Business Studies, 2023)
COVID-19 induced online class is a new experience for students in many countries like Bangladesh. This rapid shift from the conventional classroom learning environment has effects on many facets of life like psychological stress and wellbeing. In this emerging context, this study investigates the relationship between perceived academic stress of online classes, future anxiety, and psychological wellbeing with a mediation effect of optimism-one of the dimensions of psychological capital (PsyCap). In a cross-sectional design, this study collected data from 348 business students at the time of attending online classes due to social isolation in effect due to COVID-19. Using the structural equation modeling technique in the SmartPLS3.7 version, this study found that psychological wellbeing was negatively associated with online class stress and future anxiety, while positively related with optimism. The indirect effect of optimism showed that it mediated the negative impact of future anxiety-wellbeing relationships but not the online class stress-wellbeing relationship. Thus, optimism as a mechanism of PsyCap can be useful to lessen the general state of psychological wellbeing of the students during the pandemic. However, it will not be an active avenue to deal with negative causality between online class stress and wellbeing. Academic institutions need to explore effective mechanisms for curbing online class stress of the students that in turn will promote their wellbeing. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 25-45